The Influence of the Role-Playing Learning Model on the Development of Fine Motor and Arabic Vocabulary at Early Childhood Education - Ridwanulloh, M. Ubaidillah; Sari, Ainun Kartika; Donasari, Renita (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
This study aims to find out how the influence of role-playing center learning methods on fine motor and Arabic vocabulary development in early childhood in PAUD Sunan Ampel Rejomulyo Kediri. This research is a type of qualitative research that is descriptive. The data collection techniques used are interviews, observations, and documentation. The results showed that the learning method of the role-playing center starts from learning planning, then how the influence of the role-playing center learning method on the development of the role-playing center. Producing a good impact on early childhood, namely early childhood in PAUD Sunan Ampel becomes more active, because in this learning method children will learn while playing roles. This has an influence on the child's fine motor and vocabulary development. Because in a variegated play will help stimulate the child to be active, one of which is in coordinating the movements of his hands.